HUMAN CAPITAL AS A VECTOR OF MODERNIZATION OF THE ECONOMY OF KAZAKHSTAN (Journal of Economic Research & Business Administration, 2018)
The topic proposed for consideration in this article is very relevant and meets the challenges facing Kazakhstan on the way to a new growth model in the conditions of global competition. The purpose of the study is to actualize the consideration of the concept of human capital in the context of its national development in the Republic of Kazakhstan. Successful modernization is represented by further improving the quality of human capital: the growth of human productivity, the use of its talents, knowledge, competencies and other potential capabilities that allow to integrate into the national economic system and bring the desired positive effect.The scientific and practical significance of the work consists in concretizing ways to improve the quality of human capital in the process of the third modernization of Kazakhstan. The methodological basis of the study was the work of political economics classics and modern researchers of human capital. In work on the basis of the retrospective analysis of the formation of the concept of human capital, the transition from a narrow interpretation of this concept to the modern, broader one is shown. The value of the work lies in the fact that the possibilities are extended and indicators of the use of the category «human capital» in the formation of the state policy of Kazakhstan are indicated. This study can be useful to industry and government theorists and practitioners using human capital indicators in planning, analysis and evaluation.